PROFITABILITY AND OPTIMAL DEBT LEVEL OF LARGE FIRMS IN SERBIA - Milošev, Ivana (Ekonomija - teorija i praksa, 2021)
The aim of this research is to analyse the impact of debt management on the profitability of firms. The research was conducted for a five-year period from 2016 to 2020, on a sample of 299 large non-financial firms in Serbia. The Generalized Method of Moments (GMM) is used to examine the ratio of the share of total debt in total assets to the profitability expressed through the ROA indicator. The first thing considered is the linear relationship between indebtness and profitability followed by the nonlinear relationship between indebtness and profitability. The results of research show that there is a statistically significant correlation and a linear, negative ratio of indebtedness indicators in relation to the profitability of the observed firms. The results of the study do not show a nonlinear (concave) relationship. They show both negative and statistically significant impact of tangibility on the profitability of large companies in Serbia, while company size and inflation do not have a significant impact on profitability.